ANALISIS KEBERAGAMAN PRODUK DAN KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA KEDAI BABE DI SITUBONDO - Yaqin, Rizal Ainul; Sari, Lita Permata; Praja, Yudha (Fakultas Ekonomi dan Bisnis, 2023)
Marketing management can be defined as the analysis of planning, implementing and controlling programs designed to create, build and maintain profitable exchanges with target markets to achieve organizational goals. The research objective is to analyze and test the effect of product diversity and service quality on customer loyalty through customer satisfaction. The population in this study were consumers of Kedai Babe. The sampling technique was determined by the sample random sampling method. This study's data analysis and hypothesis testing used the Structural Equation Model-Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application show that product diversity has a negative but insignificant effect on customer satisfaction, service quality has a significant positive effect on customer satisfaction, product diversity has a significant positive effect on customer loyalty, service quality has a significant positive effect on customer loyalty, customer satisfaction has a positive but insignificant effect on customer loyalty, product diversity has a significant negative effect does not affect customer loyalty through customer satisfaction, service quality has a positive but insignificant effect on consumer loyalty through customer satisfaction.